Arbitration practice in construction contracts - Stephenson, Douglas A. (Oxford [England] ; Malden, MA : Blackwell Science, 2001)
Since it came into force on 31 January 1997 the Arbitration Act 1996 has generally been welcomed by users and practitioners in the construction industry. It has fulfilled expectations that it would provide a user-friendly and practical basis of resolving disputes arising from construction contracts in a fair, expeditious and economical way. In doing so it has generated a modest volume of case law that has demonstrated the excellence of the Act's provisions and its drafting. Since the Fourth Edition of this book appeared in 1997 the Housing Grants, Construction and Regeneration Act 1996 wi.
11.2 Contract documents11.3 Basic contract law; 11.4 The construction period: records; 11.5 Claims; 11.6 Adjudication; 11.7 Disputes; 11.8 Appointment of the arbitrator; 11.9 Choice of advocate; 11.10 Offers to settle; Appendices; A Specimen documents:; SD/1 Ad hoc arbitration agreement; SD/2 Application for stay of court proceedings; SD/3 Exclusion agreement; SD/4 Notice to refer and notice to concur; SD/5 Application to President to appoint an arbitrator; SD/6 Notice of appointment; SD/7 Terms of appointment; SD/8 Agenda for preliminary meeting; SD/9 Procedural directions
Includes bibliographical references (page 272) and index.
Print version record.
English.
John Wiley and Sons
Keywords: Construction contracts -- Great Britain; Civil engineering contracts -- Great Britain; Arbitration and award -- Great Britain; x; Arbitrage (Droit) -- Grande-Bretagne.; LAW -- Taxation; Arbitration and award; Civil engineering contracts; Construction contracts; Great Britain